Normal property, Jameson property, CHIP and linear regularity for an infinite system of convex sets in Banach spaces. (1st December 2016) - Wei, Zhou; He, Qinghai
Abstract : In this paper, we study different kinds of normal properties for an infinite system of arbitrarily many convex sets in a Banach space and provide the dual characterization for the normal property in terms of the extended Jameson property for arbitrarily many weak -closed convex cones in the dual space. Then, we use the normal property and the extended Jameson property to study CHIP, strong CHIP and linear regularity for the infinite case of arbitrarily many convex sets and establish equivalent relationship among these properties. In particular, we extend main results by Bakan et al. [Trans. Am. Math. Soc. 357;2005:3831–3863] on these concepts for finite system of convex sets in a Hilbert space to the infinite case of arbitrarily many convex sets in Banach space setting.